2009
DOI: 10.1111/j.1749-6632.2008.03691.x
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Proinflammatory Allele in Prostate Cancer Risk

Abstract: Prostate cancer (PCa) is the most common malignant neoplasm in older men in Western countries. The number of affected older men is increasing. Therefore, strategies for prevention of prostate cancer are crucial. To this purpose it is essential to know the mechanisms involved in development and progression of this malignancy. Recently, an increasing body of genetic and epidemiological studies proposed new hypotheses for prostate carcinogenesis. It has been suggested that genetic factors as well as exposure to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Another chemokine receptor CCR5, which is expressed on a broad spectrum of immune cells ( 84 ), interacts with its ligands CCL3, CCL4, and CCL5 ( 89 ). Interestingly, the patients with a mutated CCR5 variant were reported to be resistant to the prostate cancer development ( 90 ). Furthermore, CCR5 has a critical role in tumor progression since it has been shown that the CCR5–CCL5 axis supported tumor growth, invasion, and migration of MDSC to the tumor site ( 87 , 91 ).…”
Section: Blocking Mdsc Traffickingmentioning
confidence: 99%
“…Another chemokine receptor CCR5, which is expressed on a broad spectrum of immune cells ( 84 ), interacts with its ligands CCL3, CCL4, and CCL5 ( 89 ). Interestingly, the patients with a mutated CCR5 variant were reported to be resistant to the prostate cancer development ( 90 ). Furthermore, CCR5 has a critical role in tumor progression since it has been shown that the CCR5–CCL5 axis supported tumor growth, invasion, and migration of MDSC to the tumor site ( 87 , 91 ).…”
Section: Blocking Mdsc Traffickingmentioning
confidence: 99%
“…Individuals with a functional mutation in CCR5 (deletion of the N-terminal 32 nucleotides) display a high state of HIV resistance (63). Later, it was found that they also show low prevalence of cancer diseases, particularly cancer of the prostate (64). This motivated us to explore the underlying mechanism by which the absence of CCR5 confers cancer resistance.…”
Section: The Recruitment Of Mdsc At Tumor Sites As a Multistep Event mentioning
confidence: 99%
“…Hence, our results demonstrated, for the first time, a role of Glo2 in prostate tumorigenesis as well as suggesting a possible mechanism. Both genetic and environmental factors participate in PCa pathogenesis [ 121 , 122 ]. Nevertheless, the molecular biology and mechanisms of prostate carcinogenesis remain to be further elucidated in order to identify additional diagnostic factors.…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%